An Estimation of Earthquake Impact to Population in Makassar by Probabilistic Approach - Sunardi, Bambang; Sulastri, Sulastri (Universitas Muhammadiyah Surakarta, 2016)
Makassar is one of Indonesian big cities with rapid growth rate, but not totally safe from earthquake hazard. This condition led study on affected population by earthquakes in this city are important to do. This paper estimated the population of Makassar City threatened by the probabilistic earthquake hazard. In this current study, earthquake hazard in the forms of peak ground acceleration (PGA) and spectral acceleration, Â estimated by using Probabilistic Seismic Hazards Analysis (PSHA). The PSHA result then overlaid with administration map and population data to obtain distribution and percentage of population threatened by the probabilistic earthquake hazard. The results showed the smallest value of ground acceleration located in the south-west (Tamalate sub district), further north increased and reached the highest value in the northeast (Biring Kanaya sub district). Both Tamalate and Biringkanaya can be classified as rural area with low population density.Â The urban area of Makassar, which is the concentration of population, located in the centre of Makassar, got the middle earthquake hazard.